2018
DOI: 10.18542/ragros.v10i2.5198
|View full text |Cite
|
Sign up to set email alerts
|

Características Morfométricas, Rendimento De Filé E Composição Química Da Traíra

Abstract: Objetivou-se com este trabalho avaliar as características morfométricas, rendimento de filé e composição química da traíra (Hoplias malabaricus) com diferentes pesos. Foram utilizadas dezesseis traíras, em que os tratamentos (T) foram em função do peso vivo dos animais constituídos por T1: traíra entre 0,400 e 0,550 kg e T2: traíra entre 0,600 e 0,800 kg, distribuídos em um delineamento inteiramente casualizado. O comprimento total e padrão aumentaram (P<0,05) à medida que se elevou o peso de abate. Houve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Regarding the centesimal composition, we obtained values similar to those obtained by Santos et al (2001) and Araújo et al (2018), who analyzed the centesimal composition of uninfected H. malabaricus. In our comparison between infected and uninfected fish, we did not find any significant differences between the groups.…”
Section: Fish Yieldsupporting
confidence: 87%
“…Regarding the centesimal composition, we obtained values similar to those obtained by Santos et al (2001) and Araújo et al (2018), who analyzed the centesimal composition of uninfected H. malabaricus. In our comparison between infected and uninfected fish, we did not find any significant differences between the groups.…”
Section: Fish Yieldsupporting
confidence: 87%
“…In the Amazon region, there is marked seasonality in the moisture and fat levels of fish. During the flood season, fat levels are higher, reaching up to 15% in whole fish and 5% in filets, while moisture content can be between 65% and 75%, respectively (Junk, 1985;Mafra et al, 2016;Araújo et al, 2018). Moisture and lipid content were inversely proportional in the dry season and flood period for the L. frederici and A. ocellatus.…”
Section: Discussionmentioning
confidence: 99%
“…A 'clean body' refers to a fish specimen without the head, viscera, The morphometry of fish species influences the yield of filets and left-overs, and is data required by the fishing industry to avoid waste and add value to new byproducts. Studies by Araújo et al (2018) evaluated the yields of traíra filets (Hoplias malabaricus) during the dry season and found they made up 34.62% to 34.76% of the total weight. Additionally, Mafra et al (2016) reported a percentage yield of filet with skin of 44.79% to 48.60% for red piranha (Pygocentrus nattereri).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations